Borane Adducts of Hydrazoic Acid and Organic Azides: Intermediates for the Formation of Aminoboranes. Issue 20 (4th April 2019) - Bläsing, Kevin; Bresien, Jonas; Labbow, René; Michalik, Dirk; Schulz, Axel; Thomas, Max; Villinger, Alexander
Abstract: The reaction of HN3 with the strong Lewis acid B(C6 F5 )3 led to the formation of a very labile HN3 ⋅B(C6 F5 )3 adduct, which decomposed to an aminoborane, H(C6 F5 )NB(C6 F5 )2, above −20 °C with release of molecular nitrogen and simultaneous migration of a C6 F5 group from boron to the nitrogen atom. The intermediary formation of azide–borane adducts with B(C6 F5 )3 was also demonstrated for a series of organic azides, RN3 (R=Me3 Si, Ph, 3, 5‐(CF3 )2 C6 H3 ), which also underwent Staudinger‐like decomposition along with C6 F5 group migration. In accord with experiment, computations revealed rather small barriers towards nitrogen release for these highly labile azide adducts for all organic substituents except R=Me3 Si (m.p. 120 °C, T dec =189 °C). Hydrolysis of the aminoboranes provided C6 F5 ‐substituted amines, HN(R)(C6 F5 ), in good yields. Abstract : Boron on a Staudinger trip : HN3 reacts with the strong Lewis acid B(C6 F5 )3 to give a highly labile HN3 ⋅B(C6 F5 )3 adduct, which readily decomposes above −20 °C to the aminoborane H(C6 F5 )NB(C6 F5 )2 and N2 . This Staudinger‐like reaction, which involves a C6 F5 group migration from boron to the attached nitrogen atom, was transferred to a variety of organic azides, enabling the synthesis of C6 F5 ‐substituted aminoboranes and amines of the type H(R)N(C6 F5 ).